Nasal reconstruction in darker skin: is the subunit principle valid? - Abdulrauf, Badr M. I. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
The subunit principle of aesthetic nasal reconstruction is well known among reconstructive surgeons and it is considered to be the excellence of care. It advocates to reconstruct a nasal defect as per the specific subunit, placing the suture line at a border of one subunit and its adjacent within the nasal surface. Individuals with skin types III to V are prone to hyperpigmentation, hypertrophic scars, keloids and obvious suture marks. Applying the subunit principle in these darker complexion patients would not be sufficient. In fact, it would result in a scarred nose with a patch. With our frequent experience in such cases, it was very important to revisit the mentioned principle. In darker complexion individuals requiring significant part of their nose to be reconstructed, a consideration should be given to entire nasal unit reconstruction. This would allow placing the seams at junction with adjacent regions (cheek and lip) rather than within the nose and much acceptable aesthetic outcome.